Gynecologic oncologists’ attitudes and practices relating to integrative medicine: results of a nationwide AGO survey - Klein, Evelyn; Schütz, Florian; Wallwiener, Markus (Archives of gynecology and obstetrics, 2017)
PurposeThe growing popularity and acceptance of integrative medicine is evident both among patients and among the oncologists treating them. As little data are available regarding health-care professionals’ knowledge, attitudes, and practices relating to the topic, a nationwide online survey was designed.MethodsOver a period of 11 weeks (from July 15 to September 30, 2014) a self-administered, 17-item online survey was sent to all 676 members of the Research Group on Gynecological Oncology (Arbeitsgemeinschaft Gynäkologische Onkologie) in the German Cancer Society. The questionnaire items addressed the use of integrative therapy methods, fields of indications for them, advice services provided, level of specific qualifications, and other topics.ResultsOf the 104 respondents (15.4%) using integrative medicine, 93% reported that integrative therapy was offered to breast cancer patients. The second most frequent type of tumor in connection with which integrative therapy methods were recommended was ovarian cancer, at 80% of the participants using integrative medicine. Exercise, nutritional therapy, dietary supplements, herbal medicines, and acupuncture were the methods the patients were most commonly advised to use.ConclusionThere is considerable interest in integrative medicine among gynecological oncologists, but integrative therapy approaches are at present poorly implemented in routine clinical work. Furthermore there is a lack of specific training. Whether future efforts should focus on extending counseling services on integrative medicine approaches in gynecologic oncology or not, have to be discussed. Evidence-based training on integrative medicine should be implemented in order to safely guide patients in their wish to do something by themselves.
Published online: 8 June 2017
Gesehen am 24.10.2018